2017
DOI: 10.4103/0976-9668.210017
|View full text |Cite
|
Sign up to set email alerts
|

The role of red cell distribution width as a predictor of mortality for critically ill patients in an inner-city hospital

Abstract: Background:Red cell distribution width (RDW) is a measure of the variation in the red blood cell volume that is usually recorded as a part of the standard complete blood cell count. Recent studies have demonstrated the prognostic value of RDW in many different clinical settings. The objective of this research study is to investigate the independent association of RDW with 30-day mortality in Intensive Care Unit (ICU) patients.Methods:One hundred and fifty-six patients admitted to the ICU of our hospital betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…6,18 Similarly several studies have been conducted on children in paediatric intensive care units which have also found an association of high RDW with mortality. 5,[13][14][15]19,20 However some other studies have found that there is no relation between high RDW and mortality in children. 13,21 Said et al also found a significant relation between admission RDW as well as relative RDW (calculated as the difference between the first day RDW and highest of the first seven days RDW divided by admission RDW) with mortality.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…6,18 Similarly several studies have been conducted on children in paediatric intensive care units which have also found an association of high RDW with mortality. 5,[13][14][15]19,20 However some other studies have found that there is no relation between high RDW and mortality in children. 13,21 Said et al also found a significant relation between admission RDW as well as relative RDW (calculated as the difference between the first day RDW and highest of the first seven days RDW divided by admission RDW) with mortality.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4] But in recent years, there has been considerable interest in its use as a predictive marker of adverse outcomes in several adult diseases like autoimmune diseases, sepsis, cardiac and pulmonary diseases, operative diseases and critical illnesses. [3][4][5][6][7][8][9][10][11] Many such studies have shown promising use of RDW as a predictive marker of mortality in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers suggested that the use of this parameter as an inexpensive prognostic marker in addition to other scores such as APACHE improves the prognostication of patients, especially critically ill ones. 7,[57][58][59] conclusIon It seems that this simple and inexpensive test provides valuable information about the general health status, different diseases, clinical outcomes, complications, and mortality, regardless of the underlying disorder. Therefore, patients with increased RDW values should be more closely and intensively managed to improve their clinical outcomes.…”
Section: Red Cell Distribution Width a S A Risk Factor F O R Mortalitymentioning
confidence: 99%
“…Thrombocytopenia was defined as platelet count of <150,000 per microliter of blood ( 18 ), and sub-classified as mild (101,000-140,000/microliter), moderate (51,000-100,000/microliter), severe (21,000-50,000/microliter) and very severe (≥20,000). High red cell distribution width (RDW) was defined as > 15.5% ( 19 ).…”
Section: Methodsmentioning
confidence: 99%